2019
DOI: 10.3390/f10100932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Successive Rotations, Clear-Cutting and Stand Age of Prince Rupprecht’s larch (Larix principis-rupprechtii Mayr) on Soil Quality

Abstract: A decline in soil quality is a major factor contributing to the degradation of forest ecological function. Vegetation plays a vital role in maintaining soil quality; however, the influence of plantation length on soil quality remains unclear. In this study, we collected soil samples in Northern China using a space-for-time substitution method. Soil were collected from control grassland; a clear-cutting site; 16-year-old (young, first, and second generation), 28-year-old (immature, first, and second generation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…plantations markedly reduced the SOC content as compared with abandoned lands, but the SOC content did not vary with plum plantation age; however, the cumulative and potential SOC mineralization rates were different among plum plantation ages, and both increased with increasing soil calcium concentration; thus, more attention should be paid in the future to the critical role of calcium in SOC mineralization in the studied subtropical area [17]. In contrast, the study conducted by Zhao et al in a larch (Larix principis-rupprechtii Mayr) forest showed that the contents of SOC, total N and total K were all increased with increasing stand age, and clear-cutting reduced SOC, total N, and total K contents [18]. The effect of the conversion of natural evergreen broadleaved forests to an assisted natural regeneration and Chinese fir (Cunninghamia lanceolata (Lamb.)…”
mentioning
confidence: 74%
“…plantations markedly reduced the SOC content as compared with abandoned lands, but the SOC content did not vary with plum plantation age; however, the cumulative and potential SOC mineralization rates were different among plum plantation ages, and both increased with increasing soil calcium concentration; thus, more attention should be paid in the future to the critical role of calcium in SOC mineralization in the studied subtropical area [17]. In contrast, the study conducted by Zhao et al in a larch (Larix principis-rupprechtii Mayr) forest showed that the contents of SOC, total N and total K were all increased with increasing stand age, and clear-cutting reduced SOC, total N, and total K contents [18]. The effect of the conversion of natural evergreen broadleaved forests to an assisted natural regeneration and Chinese fir (Cunninghamia lanceolata (Lamb.)…”
mentioning
confidence: 74%
“…Huong et al (2015) identified an opportunity to increase and sustain production of tree plantations over at least three rotations through better management practices. For example, in Eucalyptus and Prince Ruprecht's larch, Zhang et al (2015) and Zhao et al (2019) observed a long‐term improvement in soil quality with reduced soil disturbance during logging, keeping understory coverage and litter retention. These general recommendations need to be tested under local agronomic constraints (e.g., pest pressures) and socio‐economic bottlenecks (e.g., shortfall in timber sales) that have to be included in any changes made in smallholder plantations.…”
Section: Discussionmentioning
confidence: 99%
“…where S is the score of soil indicator, a reflects the maximum value reached by the function (a = 1), x is the value of the indicator, x 0 is mean value of each soil indicator, and b is the value of the equation's slope. Using b = −2.5, the value provided curves that vary between 0 and 1 in a suitable way [34,35].…”
Section: Evaluation Of Soil Quality Indexmentioning
confidence: 99%